ANTIBIOTIC MISUSE AND ANTIMICROBIAL RESISTANCE KNOWLEDGE AMONG UNIVERSITY STUDENTS IN BANGLADESH: CURRENT TRENDS AND FUTURE PROSPECTS - Bhuiyan, Md. Rimon; Ali, Md. Niamot; Hiya, Nazmush Shayer; Khatun, Asma; Shafiq, Sadia Binte; Shimi, Syeda Shamapika Ahmed; Fahim, Md Muhtasim Munif; Hasan, Imtiaj (Science Journal of University of Zakho, 2026)
Antimicrobial resistance (AMR) is a growing global health concern threatening both human and animal health. Misuse and overuse of antibiotics, especially through self-medication, are major contributors in developing countries. This study aimed to assess the knowledge, attitude, and practices regarding antibiotic misuse and AMR among university students in Bangladesh. A cross-sectional questionnairebased survey was conducted from September 2024 to February 2025 among 398 students from different disciplines at the University of Rajshahi. Systematic random sampling was applied, and the data were analyzed by using SPSS, version 27, to identify associations with socio-demographic factors. Overall knowledge of antibiotics and AMR was unsatisfactory. While 90.7% of students knew about antibiotics, only 64.07% and 63.32% were aware of antimicrobial drugs and AMR, respectively. Science students showed significantly higher AMR awareness (p<0.001) than arts and commerce students. About 46.33% practiced self-medication, with males being more prone (p=0.001). Moreover, 40.25% used antibiotics irregularly, and 45.57% stopped treatment once they felt better. Arts students were more likely to discontinue antibiotic courses (p=0.001). Despite moderate awareness, the high prevalence of self-medication and inappropriate antibiotic use among university students remains alarming and highlights the urgent need for targeted educational actions to promote rational antibiotic use.